Role of Dose Intensification for Salvage Radiation Therapy after Radical Prostatectomy - Beck, Marcus; Barelkowski, Tomasz; Kaul, David; Wecker, Sascha; Thieme, Alexander H.; Zwahlen, Daniel R.; Wust, Peter; Aebersold, Daniel M.; Budach, Volker; Ghadjar, Pirus (Frontiers in Oncology, 2016)
For primary radiation therapy of prostate cancer dose intensification is established as standard of care. Less is known on the role of dose intensification in the post-prostatectomy setting for salvage radiation therapy. Thus, we aimed to identify and summarize the existing literature. In retrospective analyses dose intensified salvage radiation therapy showed a superior biochemical control compared to standard dose salvage radiation with favorable acute and late gastrointestinal and genitourinary toxicity rates, especially when modern radiation techniques such as intensity modulated radiation therapy were applied. We identified one randomized phase III trial addressing the potential benefits of dose intensified salvage radiation therapy (SAKK 09/10). Recently, acute gastrointestinal and genitourinary toxicities and early quality of life data of this trial were reported and no significant difference in acute toxicities between both treatment arms were found; however, a significant worsening of genitourinary quality of life was noted in the dose intensified treatment arm. Whereas dose intensified salvage radiation therapy appears to be feasible and well tolerated, the improved biochemical control rates using dose intensified radiation therapy as suggested by retrospective analyses have yet to be validated by prospective trials.